AKIBAT HUKUM PENDAFTARAN JAMINAN FIDUSIA DALAM SISTEM ONLINE - Made Widyari, Ida Ayu; Sirtha, I Nyoman; Sarjana, I Made (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 2 No 2 (2017), 2017)
Fiduciary security institutions are regulated through legislation, Act No. 42 of 1999. This law governs the obligation of the registration of fiduciary security in order to provide legal certainty to the interested parties and this fiduciary security registration gives the rights of preference to the fiduciary recipient of other creditors. In 2013, the Government issued a regulation to Administration System of Fiduciary Security Registration electronically in order to improve services to people who need legal services in the field of fiduciary security. Laws of Fiduciary Security are positive law applicable to the fiduciary security, but there are some things that are not regulated in the law, that is, the registration done with the online system and the legal consequences that are not registered. This study used normative legal research, which explains the existence of the absence of norms in the Law of Fiduciary Security, i.e. the registration done with the online system and the legal consequences of fiduciary security which are not registered. This study used a source of legal materials consisting of primary, secondary and tertiary legal materials. The results showed that registration of fiduciary security with the online system is regulated through the Regulation of the Minister of Justice and Human Rights of the Republic of Indonesia Number 9 of 2013 concerning the electronic imposition of Fiduciary Security and Regulation of the Minister of Justice and Human Rights of the Republic of Indonesia Number 10 of 2013 concerning the System for Registration of Fiduciary Security done Electronically. The legal consequence of the Agreement of Fiduciary Security which is not registered with the online system is that it does not produce the collateral agreement of the fiduciary security so that the collateral character such as droit de suite and the rights of preference is not inherent in the creditor of the grantor of the fiduciary security and it does not have the executorial power.